Examples and lessons for best practices for Danube River revitalisation - MARIN Eugenia; NICHERSU Iulian; MIERLĂ Marian; TRIFANOV Cristian; NICHERSU Iuliana (Scientific Annals of the Danube Delta Institute, 2012)
The ecological balance of Danube River has suffered alteration processes because of continuously development of human society. In the alteration process of the Danube have been destroyed dominating natural systems and created instead industrial structures with economical purpose such as navigation, hydro-energy, agriculture, harbours that are damaging the Danube River by losing the floodplains and natural morphological structures. In this context the necessity of enhanced measures for ecological restoration is an inevitable consequence of ecosystem degradation at functional and structural level. This paper emphasizes examples and lessons of best practices for Danube River revitalization assessed within SEE project DANUBEPARKS. In gathering the information needed, questionnaires were completed by several restoration sites along Danube River in order to develop a conceptual framework and a matrix of criteria for restoration projects assessments. The results highlighted a lack of ecological restoration projects-information data base as well as restoration ecology is still in its infancy and the literature pertinent to river restoration is rather fragmented. Many revitalization projects were planned or realized without prior knowledge of their potential for success or failure, although, theseprojects greatly contributed, as examples, to our present understanding of river-floodplain systems. Successful Danube Riverand wetland restoration demands an interdisciplinary approach in order to understand how the Danube River and Danube floodplain system function.